The Influence of Product Quality, Price, and Online Customer Reviews on the Purchase Intention of Erigo Fashion Products on Shopee among Generation Z in Surabaya - M. Adrian Fajar Maulana As. Sidik fajar; Acep Samsudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of product quality, price, and online customer reviews on the purchase intention of Erigo fashion products on Shopee among Generation Z in Surabaya. This research employs a quantitative approach using SPSS version 31. The sample consists of 157 respondents selected through purposive sampling, with data collected using structured questionnaires based on each variable’s indicators. Data analysis includes validity and reliability tests, classical assumption tests, and multiple linear regression, with hypothesis testing conducted using t-tests and F-tests.The results reveal that product quality, price, and online customer reviews have a positive and significant effect on purchase intention, both partially and simultaneously. Product quality is identified as the most dominant variable. The coefficient of determination (Adjusted R² = 0.839) indicates that 83.9% of the variation in purchase intention is explained by the independent variables. These findings highlight the importance of product quality, competitive pricing, and effective management of online customer reviews in enhancing purchase intention. This study provides practical implications for companies, particularly in the fashion e-commerce sector, in developing strategies to improve consumer purchase intention. Keywords:Product Quality, Price, Online Customer Reviews, Purchase Intention